1995
DOI: 10.1177/109019819502200108
|View full text |Cite
|
Sign up to set email alerts
|

In-Home Injury Prevention Practices for Infants and Toddlers: The Role of Parental Beliefs, Barriers, and Housing Quality

Abstract: The present research was designed to contribute to the empirical literature on the scope and determinants of parents' injury prevention practices among families living in disadvantaged, urban areas. One hundred fifty mothers were interviewed about their living environment when they brought their children (ages 6-36 months) to a hospital-based, pediatric primary care clinic. Only 37% of respondents reported that they knew their hot water temperature was 125 degrees or less. A majority (59%) of families reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 18 publications
3
58
1
Order By: Relevance
“…57 Studies in which the temperature of hot tap water was actually measured generally found higher prevalence of dangerous hot water temperatures. 51,56,[58][59][60] Only one study could be located that investigated the prevalence of installation of thermoregulation (i.e., "antiscald") devices on faucets. That study examined the residences of older adults and concluded that only 2 out of 39 total study participants had antiscald devices.…”
Section: Discussionmentioning
confidence: 99%
“…57 Studies in which the temperature of hot tap water was actually measured generally found higher prevalence of dangerous hot water temperatures. 51,56,[58][59][60] Only one study could be located that investigated the prevalence of installation of thermoregulation (i.e., "antiscald") devices on faucets. That study examined the residences of older adults and concluded that only 2 out of 39 total study participants had antiscald devices.…”
Section: Discussionmentioning
confidence: 99%
“…Where childhood injury is concerned, the differences in the environment seem to be more important for traffic injuries 14,16 and for falls or other injuries in the home setting. 17,18 Lower use of bicycle helmets seen in areas of lower socio-economic status 19 suggests that behavioural differences exist across different socio-economic levels and may play a role in some types of injuries. Certain programs (e.g., walking bus programs that allow children to walk to and from 20 may be more sustainable in affluent areas.…”
Section: Socio-economic Status and Safetymentioning
confidence: 99%
“…It was hypothesised that the proportion of parents who had adopted specific safety measures would differ between municipalities due to local injury prevention initiatives. It was also hypothesised that the adoption of child safety measures would be positively associated with the mothers' economic and educational resources.9 [13][14][15] The last issue to be examined related to: (1) the value placed on health, '6 and (2) 6 Respondents express their degree of agreement or disagreement using a six point Likert scale. Health value was measured by four items, using a seven point Likert scale.…”
mentioning
confidence: 99%